Artists in Revolution Portraits of the Russian Avant-Garde, 1905-1925 - Williams, Robert C. (Indiana University Press, 1977)
Artists in Revolution offers fresh and provocative essays on the life and art of eight leading figures of the Russian avant-garde during Russia's revolutionary age. Each of the artists made highly innovative contributions to the development of Russian (and some, indeed, to world) cultureduring this period, and the book utilizes both the traditional approaches of intellectual history and biography and some statistical and psychohistorical characterizations of larger groups of artists.